Business revival through operational process re-engineering: the case of Permint Plywood Sdn. Bhd. / Nor Azman Hasan, Syamsilawani Saari@Dahari & Zahidah Shikh Anuar - Hasan, Nor Azman; Saari@Dahari, Syamsilawani; Shikh Anuar, Zahidah (2008)
Strong demand for plywood products has probably lured manufacturers to increase their production. This has also being an eye opener for us to study on the plywood products potential and to re-engineer the existing business. We are trying to focus on the issue of business revival through operational business re-engineering. Issues on marketing and production strategy were also touched. Overall data was analyzed from primary data sources as well as individuals who serve the group and the company. Analysis was purely based on the data-driven analytical services such as unstructured interviews to reveal the major attributes related to the ceased of the operation of Permint Plywood Sdn. Bhd. Our findings revealed that, inconsistent logs supply from KPKKT and weak marketing strategy have contributed to the business shut down in December 2004.